Graphene-Based Sensors for Small Molecule Determination in Real Samples - Brito-Ramírez, T (Elsevier Inc., 2021)
Graphene-derived materials (GDMs), such as graphene oxide (GO) and reduced graphene oxide (RGO), have attracted considerable interest in the development of biosensors for small molecules. The valuable physical, chemical, and optical properties make GDMs desirable materials for sensing applications since they can be functionalized with multiple recognition molecules and enhance the transduced detection signal. This review summarizes the reports from the past five years in which GO and RGO have been used to construct electrochemical and optical sensors for food and environmental analytes. In the beginning, we briefly describe the GO and RGO synthesis methods and their specific functionalization with some organic and inorganic materials. The advances in electrochemical sensors for real food and environmental samples are discussed separately according to the type of recognition molecule and hybrid material. Subsequently, the surface plasmon resonance technique and micromotor tools based on GDM are also discussed as new optical sensors. Finally, future research prospects to advances toward effective real sample detection for electrochemical and optical sensors using GO and RGO are presented. © 2021 Elsevier B.V.